2018
DOI: 10.1080/16000870.2018.1453215
|View full text |Cite
|
Sign up to set email alerts
|

Shear dispersion and delayed propagation of temperature anomalies along the Norwegian Atlantic Slope Current

Abstract: Using satellite altimetric sea surface height (ADT) data, we search for propagation of hydrographic anomalies along the Norwegian Atlantic Slope Current (NwASC) from the Svinøy section in the south to the Fram Strait in the north. Our analyses indicate that ADT anomalies, related to low-frequency temperature variations, propagate downstream with speeds of about 2 cm s −1. Notably, this speed is nearly an order of magnitude slower than the speed of the NwASC, which in agreement with previously estimated propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
(118 reference statements)
1
12
1
Order By: Relevance
“…Compatible with these results are the findings of, for example, Chafik et al (2015) and Holliday et al (2008), who showed that temperature anomalies take about 1 year to reach the interior Norwegian Sea from the FSC. Broomé and Nilsson (2018) showed that the relatively slow propagation of temperature and salinity anomalies, compared to the faster downstream advection, can be explained by mixing between the boundary current and the interior region of weak mean flow.…”
Section: Discussionmentioning
confidence: 99%
“…Compatible with these results are the findings of, for example, Chafik et al (2015) and Holliday et al (2008), who showed that temperature anomalies take about 1 year to reach the interior Norwegian Sea from the FSC. Broomé and Nilsson (2018) showed that the relatively slow propagation of temperature and salinity anomalies, compared to the faster downstream advection, can be explained by mixing between the boundary current and the interior region of weak mean flow.…”
Section: Discussionmentioning
confidence: 99%
“…We find that interannual heat content anomalies in the Norwegian Sea are more related to the variable strength of the Atlantic water inflow than to temperature changes of the inflowing water. Observations nevertheless show that on multiannual to decadal time scales, temperature anomalies are able to propagate into and through the Norwegian Sea (Årthun et al, ; Broomé & Nilsson, ), something which suggests that temperature anomalies advected by the mean current could play a more important role in the heat budget on longer time scales. The time period covered by ECCOv4 is, however, too short to assess decadal variability in Norwegian Sea heat content.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the decadal-scale propagation and alongpath modification of SST anomalies along the Atlantic water pathway. This includes advection along the major currents (e.g., Furevik 2000;Krahmann et al, 2001;Årthun et al, 2017), local air-sea interaction (e.g., Saravanan and McWilliams 1998), Rossby waves (e.g., Liu et al, 1999), boundary waves (Marshall and Johnson, 2013), and shear-dispersion effects (Broomé and Nilsson 2018). This study does not aim to assess the relative importance of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%